# 9.4.1: Variation of Parameters for Higher Order Equations (Exercises)

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$

( \newcommand{\kernel}{\mathrm{null}\,}\) $$\newcommand{\range}{\mathrm{range}\,}$$

$$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$

$$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$

$$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$

$$\newcommand{\Span}{\mathrm{span}}$$

$$\newcommand{\id}{\mathrm{id}}$$

$$\newcommand{\Span}{\mathrm{span}}$$

$$\newcommand{\kernel}{\mathrm{null}\,}$$

$$\newcommand{\range}{\mathrm{range}\,}$$

$$\newcommand{\RealPart}{\mathrm{Re}}$$

$$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$

$$\newcommand{\Argument}{\mathrm{Arg}}$$

$$\newcommand{\norm}[1]{\| #1 \|}$$

$$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$

$$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\AA}{\unicode[.8,0]{x212B}}$$

$$\newcommand{\vectorA}[1]{\vec{#1}} % arrow$$

$$\newcommand{\vectorAt}[1]{\vec{\text{#1}}} % arrow$$

$$\newcommand{\vectorB}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vectorC}[1]{\textbf{#1}}$$

$$\newcommand{\vectorD}[1]{\overrightarrow{#1}}$$

$$\newcommand{\vectorDt}[1]{\overrightarrow{\text{#1}}}$$

$$\newcommand{\vectE}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash{\mathbf {#1}}}}$$

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

$$\newcommand{\avec}{\mathbf a}$$ $$\newcommand{\bvec}{\mathbf b}$$ $$\newcommand{\cvec}{\mathbf c}$$ $$\newcommand{\dvec}{\mathbf d}$$ $$\newcommand{\dtil}{\widetilde{\mathbf d}}$$ $$\newcommand{\evec}{\mathbf e}$$ $$\newcommand{\fvec}{\mathbf f}$$ $$\newcommand{\nvec}{\mathbf n}$$ $$\newcommand{\pvec}{\mathbf p}$$ $$\newcommand{\qvec}{\mathbf q}$$ $$\newcommand{\svec}{\mathbf s}$$ $$\newcommand{\tvec}{\mathbf t}$$ $$\newcommand{\uvec}{\mathbf u}$$ $$\newcommand{\vvec}{\mathbf v}$$ $$\newcommand{\wvec}{\mathbf w}$$ $$\newcommand{\xvec}{\mathbf x}$$ $$\newcommand{\yvec}{\mathbf y}$$ $$\newcommand{\zvec}{\mathbf z}$$ $$\newcommand{\rvec}{\mathbf r}$$ $$\newcommand{\mvec}{\mathbf m}$$ $$\newcommand{\zerovec}{\mathbf 0}$$ $$\newcommand{\onevec}{\mathbf 1}$$ $$\newcommand{\real}{\mathbb R}$$ $$\newcommand{\twovec}[2]{\left[\begin{array}{r}#1 \\ #2 \end{array}\right]}$$ $$\newcommand{\ctwovec}[2]{\left[\begin{array}{c}#1 \\ #2 \end{array}\right]}$$ $$\newcommand{\threevec}[3]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \end{array}\right]}$$ $$\newcommand{\cthreevec}[3]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \end{array}\right]}$$ $$\newcommand{\fourvec}[4]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}$$ $$\newcommand{\cfourvec}[4]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}$$ $$\newcommand{\fivevec}[5]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}$$ $$\newcommand{\cfivevec}[5]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}$$ $$\newcommand{\mattwo}[4]{\left[\begin{array}{rr}#1 \amp #2 \\ #3 \amp #4 \\ \end{array}\right]}$$ $$\newcommand{\laspan}[1]{\text{Span}\{#1\}}$$ $$\newcommand{\bcal}{\cal B}$$ $$\newcommand{\ccal}{\cal C}$$ $$\newcommand{\scal}{\cal S}$$ $$\newcommand{\wcal}{\cal W}$$ $$\newcommand{\ecal}{\cal E}$$ $$\newcommand{\coords}[2]{\left\{#1\right\}_{#2}}$$ $$\newcommand{\gray}[1]{\color{gray}{#1}}$$ $$\newcommand{\lgray}[1]{\color{lightgray}{#1}}$$ $$\newcommand{\rank}{\operatorname{rank}}$$ $$\newcommand{\row}{\text{Row}}$$ $$\newcommand{\col}{\text{Col}}$$ $$\renewcommand{\row}{\text{Row}}$$ $$\newcommand{\nul}{\text{Nul}}$$ $$\newcommand{\var}{\text{Var}}$$ $$\newcommand{\corr}{\text{corr}}$$ $$\newcommand{\len}[1]{\left|#1\right|}$$ $$\newcommand{\bbar}{\overline{\bvec}}$$ $$\newcommand{\bhat}{\widehat{\bvec}}$$ $$\newcommand{\bperp}{\bvec^\perp}$$ $$\newcommand{\xhat}{\widehat{\xvec}}$$ $$\newcommand{\vhat}{\widehat{\vvec}}$$ $$\newcommand{\uhat}{\widehat{\uvec}}$$ $$\newcommand{\what}{\widehat{\wvec}}$$ $$\newcommand{\Sighat}{\widehat{\Sigma}}$$ $$\newcommand{\lt}{<}$$ $$\newcommand{\gt}{>}$$ $$\newcommand{\amp}{&}$$ $$\definecolor{fillinmathshade}{gray}{0.9}$$

## Q9.4.1

In Exercises 9.4.1-9.4.21 find a particular solution, given the fundamental set of solutions of the complementary equation.

1. $$x^3y'''-x^2(x+3)y''+2x(x+3)y'-2(x+3)y=-4x^4$$; $$\{x,\,x^2,\,xe^x\}$$

2. $$y'''+6xy''+(6+12x^2)y'+(12x+8x^3)y=x^{1/2}e^{-x^2}$$; $$\{e^{-x^2},\,xe^{-x^2},\,x^2e^{-x^2}\}$$

3. $$x^3y'''-3x^2y''+6xy'-6y=2x$$; $$\{x,x^2,x^3\}$$

4. $$x^2y'''+2xy''-(x^2+2)y'=2x^2$$;$$\{1,\,e^x/x,\,e^{-x}/x\}$$

5. $$x^3y'''-3x^2(x+1)y''+3x(x^2+2x+2)y'-(x^3+3x^2+6x+6)y=x^4e^{-3x}$$;$$\{xe^x,\,x^2e^x,\,x^3e^x\}$$

6. $$x(x^2-2)y'''+(x^2-6)y''+x(2-x^2)y'+(6-x^2)y=2(x^2-2)^2$$; $$\{e^x,\,e^{-x},\,1/x\}$$

7. $$xy'''-(x-3)y''-(x+2)y'+(x-1)y=-4e^{-x}$$; $$\{e^x,\,e^x/x,\,e^{-x}/x\}$$

8. $$4x^3y'''+4x^2y''-5xy'+2y=30x^2$$; $$\{\sqrt x,\,1/\sqrt x,\,x^2\}$$

9. $$x(x^2-1)y'''+(5x^2+1)y''+2xy'-2y=12x^2$$; $$\{x,\,1/(x-1),\,1/(x+1)\}$$

10. $$x(1-x)y'''+(x^2-3x+3)y''+xy'-y=2(x-1)^2$$; $$\{x,\,1/x,e^x/x\}$$

11. $$x^3y'''+x^2y''-2xy'+2y=x^2$$; $$\{x,\,x^2,\,1/x\}$$

12. $$xy'''-y''-xy'+y=x^2$$; $$\{x,\,e^x,\,e^{-x}\}$$

13. $$xy^{(4)}+4y'''=6 \ln |x|$$; $$\{1,\,x,\,x^2,\,1/x\}$$

14. $$16x^4y^{(4)}+96x^3y'''+72x^2y''-24xy'+9y=96x^{5/2}$$; $$\{\sqrt x,\,1/\sqrt x,\,x^{3/2},\,x^{-3/2}\}$$

15. $$x(x^2-6)y^{(4)}+2(x^2-12)y'''+x(6-x^2)y''+2(12-x^2)y'=2(x^2-6)^2$$;$$\{1,\,1/x,\,e^x,\,e^{-x}\}$$

16. $$x^4y^{(4)}-4x^3y'''+12x^2y''-24xy'+24y=x^4$$; $$\{x,\,x^2,\,x^3,\,x^4\}$$

17. $$x^4y^{(4)}-4x^3y'''+2x^2(6-x^2)y''+4x(x^2-6)y'+(x^4-4x^2+24)y=4x^5e^x$$;$$\{xe^x,\,x^2e^x,\,xe^{-x},\,x^2e^{-x}\}$$

18. $$x^4y^{(4)}+6x^3y'''+2x^2y''-4xy'+4y=12x^2$$; $$\{x,x^2,1/x,1/x^2\}$$

19. $$xy^{(4)}+4y'''-2xy''-4y'+xy=4e^x$$; $$\{e^x,\,e^{-x},\,e^x/x,\,e^{-x}/x\}$$

20. $$xy^{(4)}+(4-6x)y'''+(13x-18)y''+(26-12x)y'+(4x-12)y=3e^x$$; $$\{e^x,\,e^{2x},\,e^x/x,\,e^{2x}/x\}$$

21. $$x^4y^{(4)}-4x^3y'''+x^2(12-x^2)y''+2x(x^2-12)y'+2(12-x^2)y=2x^5$$; $$\{x,\,x^2,\,xe^x,\,xe^{-x}\}$$

## Q9.4.2

In Exercises 9.4.22-9.4.33 solve the initial value problem, given the fundamental set of solutions of the complementary equation. Graph the solution for Exercises 9.4.22, 9.4.26, 9.4.29, and 9.4.30.

22. $$x^3y'''-2x^2y''+3xy'-3y=4x, \quad y(1)=4,\quad y'(1)=4, \quad y''(1)=2$$; $$\{x,\,x^3,\,x \ln x\}$$

23. $$x^3y'''-5x^2y''+14xy'-18y=x^3, \quad y(1)=0,\quad y'(1)=1,\quad y''(1)=7$$; $$\{x^2,\, x^3,\,x^3 \ln x\}$$

24. $$(5-6x)y'''+(12x-4)y''+(6x-23)y'+(22-12x)y=-(6x-5)^2e^x \quad \{y(0)=-4, \quad y'(0)=-{3\over2},\quad y''(0)=-19; \{e^x,\,e^{2x},\,xe^{-x} \}$$

25. $$x^3y'''-6x^2y''+16xy'-16y=9x^4, \quad y(1)=2,\quad y'(1)=1,\quad y''(1)=5$$;$$\{x,\,x^4,\,x^4 \ln |x|\}$$

26. $$(x^2-2x+2)y'''-x^2y''+2xy'-2y=(x^2-2x+2)^2, \quad y(0)=0,\quad y'(0)=5$$,$$y''(0)=0$$;$$\{x,\,x^2,\,e^x\}$$

27. $$x^{3}y'''+x^{2}y''-2xy'+2y=x(x+1), \quad y(-1)=-6,\quad y'(-1)=\frac{[4pt]}{6},\quad y''(-1)= -\frac{5}{2};\{x,\,x^2,\,1/x\}$$

28. $$(3x-1)y'''-(12x-1)y''+9(x+1)y'-9y=2e^x(3x-1)^2, \quad y(0)=\frac{3}{4},\quad y'(0)=\frac{5}{4}, \quad y''(0)=\frac{1}{4}; \{x+1,\,e^x,\,e^{3x}\}$$

29. $$(x^2-2)y'''-2xy''+(2-x^2)y'+2xy=2(x^2-2)^2, \quad y(0)=1,\quad y'(0)=-5$$,$$y''(0)=5$$;$$\{x^2,\,e^x,\,e^{-x}\}$$

30. $$x^4y^{(4)}+3x^3y'''-x^2y''+2xy'-2y=9x^2, \quad y(1)=-7,\quad y'(1)= -11,\quad y''(1)=-5,\quad y'''(1)=6; \quad \{x,\,x^2,\,1/x,\,x\ln x\}$$

31. $$(2x-1)y^{(4)}-4xy'''+(5-2x)y''+4xy'-4y=6(2x-1)^2, \quad y(0)=\frac{55}{4}, \quad y'(0)=0,\quad y''(0)=13, \quad y'''(0)=1; \{x,\,e^x,\,e^{-x},\,e^{2x}\}$$

32. $$4x^4y^{(4)}+24x^3y'''+23x^2y''-xy'+y=6x,\quad y(1)=2,\quad y'(1)=0,\quad y''(1)=4,\quad y'''(1)=-\frac{37}{4}; \{x,\sqrt x,1/x,1/\sqrt x\}$$

33. $$x^4y^4+5x^3y'''-3x^2y''-6xy'+6y=[4pt]x^3, \quad y(-1)=-1, \; y'(-1)=-7$$,

$$y''(-1)=-1,\quad y'''(-1)=-31$$; $$\{x,\, x^3,\,1/x,\,1/x^2\}$$

## Q9.4.3

34. Su[4pt]ose the equation

$P_0(x)y^{(n)}+P_1(x)y^{(n-1)}+\cdots+P_n(x)y=F(x) \tag{A}$

is normal on an interval $$(a,b)$$. Let $$\{y_1,y_2,\dots,y_n\}$$ be a fundamental set of solutions of its complementary equation on $$(a,b)$$, let $$W$$ be the Wronskian of $$\{y_1,y_2,\dots,y_n\}$$, and let $$W_j$$ be the determinant obtained by deleting the last row and the $$j$$-th column of $$W$$. Su[4pt]ose $$x_0$$ is in $$(a,b)$$, let

$u_j(x)=(-1)^{(n-j)}\int_{x_0}^x{F(t)W_j(t)\over P_0(t)W(t)}\,dt, \quad 1\le j\le n,\nonumber$

and define

$y_p=u_1y_1+u_2y_2+\cdots+u_ny_n.\nonumber$

1. Show that $$y_p$$ is a solution of (A) and that $y_p^{(r)}=u_1y^{(r)}_1+u_2y_2^{(r)}\cdots+u_ny^{(r)}_n,\quad 1 \le r \le n-1,\nonumber$ and $y_p^{(n)}=u_1y_1^{(n)}+u_2y_2^{(n)}+\cdots+u_ny_n^{(n)}+{F\over P_0}.\nonumber$ HINT: See the derivation of the method of variation of parameters at the beginning of the section.
2. Show that $$y_p$$ is the solution of the initial value problem $\begin{array}{r} P_0(x)y^{(n)}+P_1(x)y^{(n-1)}+\cdots+P_n(x)y=F(x),\\[4pt] y(x_0)=0,\; y'(x_0)=0,\dots,\quad y^{(n-1)}(x_0)=0. \end{array}\nonumber$
3. Show that $$y_p$$ can be wri[4pt]en as $y_p(x)=\int_{x_0}^x G(x,t)F(t)\,dt,\nonumber$ where $G(x,t)={1\over P_0(t)W(t)}\left|\begin{array}{cccc} y_1(t)&y_2(t)&\cdots&y_n(t)\\[4pt] y_1'(t)&y_2'(t)&\cdots&y_n'(t)\\[4pt] \vdots&\vdots&\ddots&\vdots\\[4pt] y_1^{(n-2)}(t)&y_2^{(n-2)}(t)&\cdots&y_n^{(n-2)}(t)\\[4pt] y_1(x)&y_2(x)&\cdots&y_n(x)\end{array}\right|,\nonumber$ which is called the Green’s function for (A).
4. Show that ${\partial^{j}G(x,t)\over\partial x^j} ={1\over P_0(t)W(t)}\left|\begin{array}{cccc} y_1(t)&y_2(t)&\cdots&y_n(t)\\[4pt] y_1'(t)&y_2'(t)&\cdots&y_n'(t)\\[4pt] \vdots&\vdots&\ddots&\vdots\\[4pt] y_1^{(n-2)}(t)&y_2^{(n-2)}(t)&\cdots&y_n^{(n-2)}(t)\\[4pt] y_1^{(j)}(x)&y_2^{(j)}(x)&\cdots&y_n^{(j)}(x)\end{array}\right|,\quad 0\le j\le n.\nonumber$
5. Show that if $$a<t<b$$ then $\left. \frac{\partial ^{j}G(x,t)}{\partial x^{j}} \right| _{x=t} = \left\{\begin{array}{cl}{0,}&{1\leq j\leq n-2}\\[4pt]{\frac{1}{P_{0}(t)},}&{j=n-1} \end{array} \right. \nonumber$
6. Show that $y_{p}^{(j)}(x) = \left\{\begin{array}{cl}{\int_{x_{0}}^{x}\frac{\partial ^{j}G(x,t)}{\partial x^{j}}F(t)dt, }&{1\leq j\leq n-1,}\\[4pt]{\frac{F(x)}{P_{0}(x)}+\int_{x_{0}}^{x}\frac{\partial ^{(n)}G(x,t)}{\partial x^{n}}F(t)dt, }&{j=n.} \end{array} \right. \nonumber$

## Q9.4.4

In Exercises 9.4.35-9.4.[4pt] use the method suggested by Exercise 9.4.34 to find a particular solution in the form $$y_{p}=\int_{x_{0}}^{x}G(x,t)F(t)dt$$, given the indicated fundamental set of solutions. Assume that $$x$$ and $$x_{0}$$ are in an interval on which the equation is normal.

35. $$y'''+2y'-y'-2y=F(x); \quad \{e^x,\,e^{-x},e^{-2x}\}$$

36. $$x^3y'''+x^2y''-2xy'+2y=F(x); \quad \{x,\,x^2,\,1/x\}$$

37. $$x^3y'''-x^2(x+3)y''+2x(x+3)y'-2(x+3)y=F(x); \{x,x^2,xe^x\}$$

38. $$x(1-x)y'''+(x^2-3x+3)y''+xy'-y=F(x); \quad \{x,\,1/x,\,e^x/x\}$$

39. $$y^{(4)}-5y''+4y=F(x); \quad \{e^x,\,e^{-x},\,e^{2x},\,e^{-2x}\}$$

[4pt]. $$xy^{(4)}+4y'''=F(x); \quad \{1,\,x,\,x^2,\,1/x\}$$

[4pt]. $$x^4y^{(4)}+6x^3y'''+2x^2y''-4xy'+4y=F(x)$$; $$\{x,x^2,1/x,1/x^2\}$$

[4pt]. $$xy^{(4)}-y'''-4xy'+4y'=F(x); \quad \{1,\,x^2,\,e^{2x}, e^{-2x}\}$$

This page titled 9.4.1: Variation of Parameters for Higher Order Equations (Exercises) is shared under a CC BY-NC-SA 3.0 license and was authored, remixed, and/or curated by William F. Trench.